Free nicotine content and strategic marketing of moist snuff tobacco products in the United States: 2000–2006. Issue 5 (31st July 2008) - Alpert, H R; Koh, H; Connolly, G N
Abstract : Background: From 2000 to 2006, moist snuff sales have increased and now account for 71% of the smokeless tobacco market. Previous research has shown that major manufacturers of smokeless tobacco products manipulated free nicotine, the form most readily absorbed, to promote tolerance and addiction. Aim: This study examines the possibility that company-specific and brand-specific strategies of the major moist snuff manufacturers involve controlling free nicotine content and ease of dosing with products that are designed and targeted to specific groups. This study looks at the current total US moist snuff market with product design data from the Massachusetts Department of Public Health; moist snuff use from the National Survey on Drug Use and Health; market data from ACNielsen; and magazine advertising expenditures from TNS Media Intelligence. Results: (1) The levels of free nicotine of moist snuff products have increased over time for several major manufacturers; (2) the number and variety of sub-brands have increased over time; (3) changes in design, as reflected by variation in free nicotine associated with pH or tobacco leaf, or both, have enhanced the ease and uniformity of dosing; (4) marketing through price and advertising has increased; and (5) youth use has increased. Conclusion: A combination of factors including brand proliferation, control of free nicotine and product design has most likely resulted in the expanded consumption of moist snuff, particularly among young people.